From new geological paradigm to the problems of regional geological-geophysical survey - Lukin, A.; Shestopalov, V. (Geofizicheskiy Zhurnal, 2018)
Analysis of the latest scientific achievements in different areas of geological and geophysical research showed that investigation of deep Earth degassing from its core up to the surface and atmosphere acquires status of the mainstream in the Earth sciences. Of great fundamental and applied significance is identification of the most energetically active and powerful sub-vertical upward degassing processes, which generate trans-geosphere and cross-formational systems and are localized in the form of a hierarchy of different-sized degassing pipes — from the base plume to the elementary near-surface channel. Existence of this system is ensured by a series of successive exothermic transformations of elementary recovered gases into oxide substances. As a result of given chemical reactions these substances consistently receive new portions of energy sufficient for the gradual upward breakthrough of the mantle and crust internal substance. Interpretation of mantle plumes as the basic degassing mega-tubes allows us to unite the main aspects of endogenous ore formation, naphtidogenesis in the lithosphere and ecological processes in the earth’s crust and atmosphere. The cross-formational systems serve as the structural-geological basis of degassing pipes. Given systems are the basic concentrates of the naphtides upward migration and accumulation in the multi-layered deposits. The relationship between diapirism and mega-plumes derivatives — degassing pipes becomes increasingly clear. The degassing energy is the main factor of diapirism. The locations of possible anomalous degassing in Ukraine were identified based on the analysis of geophysical and other signs of modern activation. An assumption is made of possible commercial production of natural hydrogen in some of these locations. Ecological risks of deep Earth degassing, in particular, catastrophic degassing through super volcanoes are considered. Possible directions of counteraction against these risks with the help of purposeful efforts of the progressive humanity are also discussed. There is a need to revise the strategy and methodology of further development of geological and geophysical researches in general and, in particular, the major applied research areas, such as complex geological survey, mapping, prospecting of mineral resources and geo-ecology.